ANALISIS KEKUATAN DAN FATIGUE LIFE PADA SHAFT PROPELLER KAPAL MENGGUNAKAN FINITE ELEMENT METHOD - Ridho Firmansyah (2023)
The propeller shaft in the propeller propulsion system functions to distribute power from the main engine to the propeller. This process undergoes various forces and loads, necessitating considerations for strength and material selection. This study aims to determine the stress values and fatigue life of the 27-meter tugboat's propeller shaft, which is made of stainless steel 304 material. As an enhancement, variations in materials, including stainless steel 316 and stainless steel 2205, are explored with different loading conditions. The analysis employs the finite element method assisted by static structural analysis to conduct the finite element analysis. The values of von Mises stress and the shortest fatigue cycles are obtained through the simulation process. The analysis reveals that the von Mises stress values for stainless steel 316, under 100% loading, are 202 MPa, 181.39 MPa for 90%, and 101.3 MPa for 50% loading. The fatigue life for stainless steel 316 is determined to be 14.70 years, 21.73 years, and 23.36 years, respectively. For stainless steel 304, the von Mises stress values under 100%, 90%, and 50% loading are 207.41 MPa, 187.15 MPa, and 104.39 MPa, with corresponding fatigue lives of 13.29 years, 21.92 years, and 19.68 years. In the case of stainless steel 2205, the von Mises stress values are 201.45 MPa 100% loading, 301.84 MPa 150% loading, and 402.65 MPa 200% loading. The fatigue life for stainless steel 2205 is determined to be 14.79 years, 21.73 years, 23.58 years, 3.82 years, and 3.79 years.